1997
DOI: 10.1073/pnas.94.26.14707
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus X protein and p53 tumor suppressor interactions in the modulation of apoptosis

Abstract: We have reported previously that the hepatitis B virus oncoprotein, HBx, can bind to the C terminus of p53 and inhibit several critical p53-mediated cellular processes, including DNA sequence-specific binding, transcriptional transactivation, and apoptosis. Recognizing the importance of p53-mediated apoptosis for maintaining homeostasis and preventing neoplastic transformation, here we further examine the physical interaction between HBx and p53 as well as the functional consequences of this association. In vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
213
3
4

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(225 citation statements)
references
References 49 publications
5
213
3
4
Order By: Relevance
“…Thus, cell-type speci®cities might account for the discrepancy between our results and the reported requirement for p53 in mediating HBx-induced cell death in NIH3T3 cells (Chirillo et al, 1997). The interaction of HBx with p53 and the contrasting ability of HBx to block p53-induced apoptosis (Elmore et al, 1997;Wang et al, 1995) were not addressed in this study.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Thus, cell-type speci®cities might account for the discrepancy between our results and the reported requirement for p53 in mediating HBx-induced cell death in NIH3T3 cells (Chirillo et al, 1997). The interaction of HBx with p53 and the contrasting ability of HBx to block p53-induced apoptosis (Elmore et al, 1997;Wang et al, 1995) were not addressed in this study.…”
Section: Discussioncontrasting
confidence: 66%
“…There is also evidence to indicate that HBx may bind a variety of cellular target genes (Fischer et al, 1995;Lee et al, 1995;Sirma et al, 1998), and notably the tumor suppressor protein p53 (Feitelson et al, 1993;Lin et al, 1997;Ueda et al, 1995). HBx was shown to sequester the p53 protein in the cytoplasm and to inactivate its transactivating and apoptotic properties (Elmore et al, 1997;Takada et al, 1997;Truant et al, 1995;Wang et al, 1994Wang et al, , 1995. In other reports however, inhibition of known cellular functions of p53 could not be evidenced in cells with replicative HBV (Puisieux et al, 1995), and the apoptotic activity of the X gene product was found to require wild-type p53 (Chirillo et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…HBV-X stimulates cell cycle progression, shortening the emergence of cells from quiescence (G0) and entry into S phase and accelerating transit through checkpoint controls at G0/G1 and G2/M thus participate in the selection of cells that are genetically unstable, some of which would accumulate unrepaired transforming mutations (Benn and Schneider, 1995). Modulation of the apoptosis by the interactions of HBV-X protein and p53 gene product has also been reported (Elmore et al, 1997;Takada et al, 1997;Wang et al, 1994). Anti-apoptotic actions of HBV-X protein as a potent caspase 3 inhibitor has been described (Gottlob et al, 1998).…”
Section: Discussionmentioning
confidence: 95%
“…A direct dose-dependent apoptotic function of HBV-X has been demonstrated in transiently transfected liver cell lines (Terradillos et al, 1998). HBV-X protein acutely sensitizes cells to apoptotic killing when expressed during viral replication independent of other genes (Werness et al, 1990;Su and Schneider, 1997;Slagle et al, 1996;Elmore et al, 1997). Cells that were resistant to apoptotic killing by high doses of tumor necrosis factor-a, a cytokine associated with liver damage during HBV infection, were made sensitive to very low doses of TNF-alpha by HBV-X (Su and Schneider, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the adenovirus E1B-55-kDa protein anchors p53 in cytoplasmic structures, reducing p53 transcriptional activity (Blair Zajdel and Blair, 1988;Konig et al, 1999;Sarnow et al, 1982;Yew and Berk, 1992;Zantema et al, 1985). The hepatitis B virus HBx protein localizes p53 to the cytoplasm and inhibits both its transcriptional activity and its ability to mediate apoptosis (Elmore et al, 1997;Feitelson et al, 1993;Ueda et al, 1995;Wang et al, 1994Wang et al, , 1995. Hepatocellular carcinoma is among the most common malignancies world wide, with over 80% of patients positive for Hepatitis B virus infection.…”
Section: Linking P53 Activation With Its Subcellular Localizationmentioning
confidence: 99%